ANALISIS VARIASI PRODUK, KUALITAS PELAYANAN DAN WOM TERHADAP KEPUTUSAN PEMBELIAN CAFE NDALEM SIMBAH - Putra, Cahya Illafi Rochmana; Samari, Samari; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2022)
The current research has an interest in knowing the relationship between product variations, service quality and purchasing decisions at Ndalem Simbah cafe. The study uses a causal quantitative approach, with primary data distributed boldly to respondents. The sample used in this study were visitors to the Ndalem Simbah cafe, with a total of 40 respondents. By using validity, reliability, classical assumptions, multiple linear regression analysis, hypothesis testing using t test and f test, and coefficient of determination with the help of the SPSS 23 program. The results obtained by word of mouth partially have no effect on purchasing decisions with a sig value 0.784 , but product variations and service quality have a significant effect on purchasing decisions with sig values ​​of 0.012 and 0.000. Meanwhile, simultaneously product variation, service quality and word of mouth have a significant effect with a sig value of 0.000.